Deregulated hypoxic response in myeloid cells: A model for high‐altitude pulmonary oedema (HAPE). (16th March 2020) - Gojkovic, Milos; Darmasaputra, Gabriella S.; Veliça, Pedro; Rundqvist, Helene; Johnson, Randall S.
Abstract: Aim: High‐altitude pulmonary oedema (HAPE) is a non‐cardiogenic pulmonary oedema that can occur during rapid ascent to a high‐altitude environment. Classically, HAPE has been described as a condition resulting from a combination of pulmonary vasoconstriction and hypertension. Inflammation has been described as important in HAPE, although as a side effect of pulmonary oedema rather than as a causative factor. In this study, we aim to understand the role of hypoxic response in myeloid cells and its involvement in pathogenesis of HAPE. Methods: We have generated a conditional deletion in mice of the von Hippel‐Lindau factor (VHL) in myeloid cells to determine the effect of a deregulated hypoxic response in pulmonary oedema. Results: The deletion of VHL in pulmonary myeloid cells gave rise to pulmonary oedema, increased pulmonary vascular permeability and reduced performance during exertion. These changes were accompanied by reduced stroke volume in the left ventricle. Conclusion: In this model, we show that a deregulated myeloid cell hypoxic response can trigger some of the most important symptoms of HAPE, and thus mice with a deletion of VHL in the myeloid lineage can function as a model of HAPE.